Principle of ultra precision polishing with micro water mist for KDP/DKDP crystals. (2015) - Gao, Hang; Song, Chengpeng; Guo, Dongming
Potassium dihydrogen phosphate (KDP) or deuterated potassium dihydrogen phosphate (DKDP) crystals are difficult to machine because they are soft and hygroscopic. Based on the deliquescence nature of KDP/DKDP crystals, a novel polishing method with micro water mist for KDP/DKDP crystals was proposed in this paper. The processing principle was investigated and polishing experiments with this method were carried out. The results show that the crystals can be machined by this method and the maximum material removal rate can reach 2.02 µm/min. A polished surface with root-mean-square roughness 47.6 nm was achieved by polishing with micro water mist in 10 min. The material removing principle and the planarisation mechanism were experimentally explained and verified.